Impact of productivity drivers on the performance of manufacturing firms - Elijah Adeyinka, Adedeji; Michael, ADELOWOTAN (Edelweiss Applied Science and Technology, 2024)
A considerable number of research indicates that a nation’s industrial sector plays a crucial role in its economic growth. Therefore, it is crucial to research the productivity drivers among businesses engaged in the manufacturing sector to create a sound, inclusive, long-lasting, and innovative industry. Thus, as a micro-perspective of industrialization, this study looks into the main productivity drivers of manufacturing firms in Nigeria. The study analyses an imbalanced panel firm-level dataset from 2007 to 2019 using the simultaneous approach of the stochastic frontier to achieve its goal. Our research shows that Nigerian manufacturing firms deal with growing returns to scale and a high labour intensity. For policy actions, it was recommended that a realistic industrialization strategy has to be micro-founded. This strategy should prioritise large-scale industrial companies, promote exports, and provide a steady supply of electricity. The findings also show that small and micro firms in Nigeria are more productive than large manufacturing firms, even though the frequency of power outages and average labour costs impede the productivity of these firms.